THE USE OF STEM CELLS IN NEUROLOGY - Jakub Przerwa (International Journal of Innovative Technologies in Social Science, 2025)
Stem cells, due to their ability to differentiate and self-renew, have found applications in various therapeutic processes, including the treatment of neurological diseases. Because the central nervous system has limited regenerative capacity, neurological disorders remain both a clinical and societal challenge. Clinical studies have shown that regenerative therapy using stem cells produces beneficial effects in the treatment of conditions such as Parkinson’s disease, Alzheimer’s disease, stroke, and spinal cord injury. However, safety concerns - including the risk of tumor formation, variable cell survival, heterogeneity of cell preparations, and lack of standardized procedures- continue to be analyzed.This article presents various sources of stem cells - embryonic stem cells (ESC), induced pluripotent stem cells (iPSC), and adult stem cells such as mesenchymal stem cells (MSC) and neural stem cells (NSC). Therapeutic mechanisms and modern technologies, including biomaterials, tissue engineering, and gene therapy, which enhance the effectiveness of cell-based therapies, are also discussed. Current applications of regenerative therapy in selected neurological disorders are presented, with particular emphasis on mechanisms of action, results from preclinical and clinical studies, and ethical and legal issues. The article highlights the need for further clinical research and for advancements enabling controlled cell differentiation.The use of stem cells may transform the understanding and treatment of neurological diseases; however, fully utilizing their potential requires further multidisciplinary research.